Covid-19 And The Communication Revolution : An Analysis Of Student Social Change In Higher Education - istiani, Ade nur; MANSYUR, M (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
Abstract The purpose of this study is to analyze the communication revolution and social changes the impact of the Covid-19 pandemic in the higher education environment. This research uses the close theory of the Communication Revolution and social change. The informant in the study was a student of the Islamic Broadcasting Communication Department of UIN Raden Intan Lampung. The research method used is a qualitative research method with a phenomenological type of study. The results showed that the impact of the communication revolution is divided into three types, namely 1. Immanent Change 2. Selective Contact Change and 3. Directed Contact Change. Meanwhile, the result of social changes that occur is a change in use 1. communication media, 2.Learning culture, 3. Communication technology insights and 4.Online culture or virtual communication.Keywords : Communication Revolution, Social Change, Covid-19